2010
DOI: 10.1002/adfm.200901905
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure‐Lattice Thermal Conductivity Correlation in Nanostructured PbTe0.7S0.3 Thermoelectric Materials

Abstract: The reduction of thermal conductivity, and a comprehensive understanding of the microstructural constituents that cause this reduction, represent some of the important challenges for the further development of thermoelectric materials with improved figure of merit. Model PbTe‐based thermoelectric materials that exhibit very low lattice thermal conductivity have been chosen for this microstructure–thermal conductivity correlation study. The nominal PbTe0.7S0.3 composition spinodally decomposes into two phases: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
260
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 311 publications
(272 citation statements)
references
References 47 publications
11
260
1
Order By: Relevance
“…These results denote that phonon scattering has occurred due to disorder rising from solute atoms in solid solution as discussed above, and also through interfaces of the lamellar pattern. Although the interlamellar spacing has been increased by equilibration at high temperatures, compared to previous studies, 17 phonon scattering by boundaries and interfaces played a significant role in the thermal conductivity reduction.…”
Section: Transport Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…These results denote that phonon scattering has occurred due to disorder rising from solute atoms in solid solution as discussed above, and also through interfaces of the lamellar pattern. Although the interlamellar spacing has been increased by equilibration at high temperatures, compared to previous studies, 17 phonon scattering by boundaries and interfaces played a significant role in the thermal conductivity reduction.…”
Section: Transport Propertiesmentioning
confidence: 84%
“…Recent studies 7-9 11 12 have improved PbTe thermoelectric performance significantly through tuning the electronic structure and/or nanostructuring of bulk materials. However, Te is rare in the Earth's crust, used in other applications 13 and is expensive hence the focus in the latest studies [14][15][16][17] trying to replace Te with Se or S. 18 19 Sulphur is amongst the 16 most abundant elements in the Earth's crust 13 and replacing Te, partially with S also provides a fascinating opportunity to form fine lamellar microstructure through spinodal decomposition, which appears in binary phase diagrams of the PbTe-PbS system. Lamellar patterns resembling a eutectic structure have been demonstrated for several thermoelectric materials 17 20-22 and thermal conductivity reduction has been reported, specifically for PbTe-PbS system, 14 …”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent experimental studies on the strong reduction of the lattice thermal conductivity in nanostructured PbTe [9,10] emphasized the importance of dislocations, nanoscale precipitates and strain while pointing out that the mere presence of nanostructuring cannot sufficiently increase the phonon scattering. He et al [11] found that not all nanostructures favorably scatter phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Significant efforts have been made to enhance the zT value of PbTe [2][3][4][5][6][7][8][9][10][11]. By introducing resonant states, Tl doped p-type PbTe resulted in a high zT value of 1.5 at 773 K [4].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Ternary PbTe-rich alloys of PbTe-PbSe 4,17,18 show a higher figure of merit than individual binary PbTe and PbSe systems in the temperature range of 550-800 K, mainly due to alteration of the electronic band structure. 4,18 In contrast, higher zT values of PbTe-PbS [19][20][21][22] compared to the binary systems are credited to the reduction in lattice thermal conductivity, which originates from phonon scattering at the interfaces of secondary phases, as PbS shows very limited solubility in the PbTe matrix. 23 Here, we present a strategy to design single-phase quaternary alloys with high thermoelectric efficiency.…”
Section: Introductionmentioning
confidence: 99%